Penguatan Penegakan Etika Pariwara Indonesia dalam Iklan Luar Griya, Studi dalam Iklan Pemilihan Walikota dan Wakil Walikota Yogyakarta - Rohmad, Muhammad Furqon Dwi Nur; Al-Azhar, Muhammad Fachrul Ikhsan; Fadli, Hanip; Muktaf, Zein Mufarrih (Jurnal Audiens, 2025)
This study aims to analyze violations of the Indonesian Advertising Ethics (EPI) in the billboard advertisements of the Yogyakarta mayoral and deputy mayoral candidates, Heroe Pena, during the 2024 election campaign. The advertisements use superlative terms such as "best," "number one," and "guaranteed," which have the potential to mislead audiences without accompanying evidence. This research employs a descriptive qualitative method to explore the occurrence of these violations and their impact on public perception. The study elaborates on how the language used in political advertisements can influence public perception and create claims unsupported by concrete data. By comparing these practices with the EPI guidelines, the research finds that the use of superlative terms in the Heroe Pena advertisements violates the principles of transparency and truthfulness stipulated in advertising ethics. The findings indicate that political advertisements that do not adhere to EPI can undermine public trust and damage the candidate's image. This study highlights the importance of compliance with ethical standards in advertising, particularly in the political context, to ensure that the information conveyed to the public is honest and accurate. Therefore, this research provides significant insights into the role of ethics in political communication and its impact on the democratic process.